Gastrointestinal stromal tumours (GISTs): an insight into clinical practice with review of literature. Issue 1 (19th July 2016) - McDonnell, M J; Punnoose, S; Viswanath, Y K S; Wadd, N J; Dhar, A
Abstract : Background: Gastrointestinal stromal tumours (GISTs) are rare mesenchymal tumours of the gastrointestinal tract. We retrospectively reviewed the clinical management of all patients with GIST presenting to a regional multidisciplinary upper gastrointestinal cancer group in the north of England. Methods: Clinical, pathological, immunohistochemical treatment strategies, follow-up and outcome data on all patients with GIST between 2007 and 2012 were reviewed. Tumours were categorised by risk according to the National Institutes of Health (NIH) and AFIP models. Results: 36 (85.7%) of 42 tumours were located in the stomach, 5 (11.9%) in the small intestine and 1 (2.4%) in the oesophagus. Median age of patients was 68 (range 43–91) years. 24 patients (57.1%) were female. Tumour size ranged from 1.0  to 12.7 cm with mean size of 5.46 cm. Metastasis was present in 19 (45.2%) patients at diagnosis with distant metastases in 12 patients. Liver was the most common site of metastases. Histology and immunohistochemical analysis was available in 32 (76.2%) patients. Most common histology was spindle cell morphology 17/32 (53.1%) followed by epithelioid 9/32 (28.1%) and mixed morphology 5/32 (15.6%). The positive rate for KIT protein (CD117) was 90.6%, while that for CD34 was 75.0%. 12/25 (48.0%) and 8/23 (34.8%) patients were categorised as high risk as per NIH and AFIP risk scores, respectively. 23/42 (54.8%) patients underwent surgical resection, after which 5/23 (21.7%) had adjuvant imatinib therapy. Imatinib was given as primary therapy in 14/42 (33.3%) patients. Conclusions: Surgery alone may not be a curative treatment for GISTs. Targeted therapy with imatinib may play an important role in the treatment of GISTs. Further risk categorisation models may be needed to evaluate GIST behaviour and prognosis.